The iron regulatory capability of the major protein participants in prevalent neurodegenerative disorders - Wong, Bruce X.; Duce, James A. (Frontiers in Pharmacology, 2014)
As with most bioavailable transition metals, iron is essential for many metabolic processes required by the cell but when left unregulated is implicated as a potent source of reactive oxygen species. It is uncertain whether the brain’s evident vulnerability to reactive species-induced oxidative stress is caused by a reduced capability in cellular response or an increased metabolic activity. Either way, dys-regulated iron levels appear to be involved in oxidative stress provoked neurodegeneration. As in peripheral iron management, cells within the central nervous system tightly regulate iron homeostasis via responsive expression of select proteins required for iron flux, transport and storage. Recently proteins directly implicated in the most prevalent neurodegenerative diseases, such as amyloid-β precursor protein, tau, α-synuclein, prion protein and huntingtin, have been connected to neuronal iron homeostatic control. This suggests that disrupted expression, processing or location of these proteins may result in a failure of their cellular iron homeostatic roles and augment the common underlying susceptibility to neuronal oxidative damage that is triggered in neurodegenerative disease.